ENERGY EFFICIENCY OF A HYBRID ROAD TRAIN WITH AN ACTIVE SEMI-TRAILER FOR ROAD CONSTRUCTION WORK - Vasiliev, Alexey; Dobretsov, Roman; Voinash, Sergey; Syromiatnykov, Yurii; Orekhovskaya, Alexandra; Zagidullin, Ramil; Sokolova, Viktoriia (Journal of Applied Engineering Science, 2024)
The previous experience of creating experimental road trains with an active trailer and semi-trailer is analyzed against the background of modern technological capabilities of transport engineering and the logistical needs of modern construction. The expediency of implementing the concept of a road train with an active trailer based on modern electromechanical technologies is shown. The purpose of the study is to increase the energy efficiency of road trains used in construction for transporting long-length objects (beams, piles, bridge trusses, panels, etc.) by using an active trailer link with an electromechanical drive. The study solves the problem of modeling the movement of road trains with passive and active semi-trailers and comparing their energy efficiency and safety indicators. The methods of modeling the movement of cars and road trains, characteristic of the theory of movement of transport vehicles, approaches of theoretical mechanics and applications of differential calculus, applied numerical modeling in the SimuLink environment are used. A mathematical model has been obtained that allows calculating the energy efficiency of a road train when using passive (towed) and active semi-trailers. The cycle of the road train movement has been developed and tested for use in severe road conditions (construction with weak road infrastructure, forest complex, transportation of special cargo). The implementation of the computational model by means of the SimuLink software package is proposed. Based on the simulation results, conclusions are made on the energy efficiency and safety of road trains with an active trailer link with an electromechanical transmission.
Keywords: transportation of long structures in construction, active trailers, hybrid road train, energy consumption, all-terrain vehicles